2006
DOI: 10.3168/jds.s0022-0302(06)72072-0
|View full text |Cite
|
Sign up to set email alerts
|

Technical Note: Improved Extraction Method with Hexane for Gas Chromatographic Analysis of Conjugated Linoleic Acids

Abstract: Extraction properties of different solvents (chloroform/methanol, hexane/isopropanol, and hexane) were studied for the gas chromatographic analysis of conjugated linoleic acids (CLA) from probiotic bacteria grown in de Man, Rogosa, and Sharpe medium. As compared with chloroform/methanol and hexane/isopropanol, hexane showed comparable extraction efficiency for CLA from unspent de Man, Rogosa, and Sharpe medium, but showed minimal extraction of oleic acid originated from the emulsifier in broth. The extraction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…The culture was then centrifugated (6000 × g for 10 min at 4 °C). Four microliters CFS were extracted with 6 mL of chloroform/methanol (2:1, v/v), mixed for 3 min and allowed to settle for 30 min as described by Jung and others (2006). The chloroform/methanol phase was harvested and traces of water were removed using sodium sulphate.…”
Section: Methodsmentioning
confidence: 99%
“…The culture was then centrifugated (6000 × g for 10 min at 4 °C). Four microliters CFS were extracted with 6 mL of chloroform/methanol (2:1, v/v), mixed for 3 min and allowed to settle for 30 min as described by Jung and others (2006). The chloroform/methanol phase was harvested and traces of water were removed using sodium sulphate.…”
Section: Methodsmentioning
confidence: 99%
“…Supernatants were extracted as described by Jung et al (2006) with some modifications. Samples were extracted with 2x 500 ll n-hexane after addition of 1 g NaCl crystals to facilitate diffusion.…”
Section: Extraction and Methylationmentioning
confidence: 99%
“…Several components may be responsible, although to date investigations have revealed that two do have biological activity: namely, cis9, trans11 CLA and trans10, cis12 CLA (López Bote et al 2004;Bondia-Pons et al 2007). The cis9, trans11 isomer stimulates the growth, reduces the severity of diabetes, strengthens bones, decreases cholesterol levels, and has antiatherogenic properties (Jung et al 2006;Bondia-Pons et al 2007;Silva Hernández et al 2007;Meluchová et al 2008). In contrast, the trans10, cis12 isomer elicits a reduction in fat levels (Park et al 2007).…”
mentioning
confidence: 99%